Wear-resistant and tensile-resistant sheath material and cable

By using modified silicon nitride particles to attach tiny bumps or synapses of alumina, titanium dioxide and aluminum titanate on the surface of the cable sheath material, the problem of easy wear and scratches in harsh environments is solved, and higher wear resistance and pull resistance are achieved, extending the service life of the cable.

CN119763912APending Publication Date: 2025-04-04RUIXIN GRP CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510085449.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Traditional cable sheath materials are prone to wear and scratches in harsh environments, resulting in exposure of internal cable lines, causing safety hazards, and insufficient wear resistance and tensile resistance.

Method used

Using an abrasion-resistant and tensile-resistant sheathing material, including EVA, PE, wear-resistant filler, glass fiber and silane coupling agent, the specific surface area and binding stability are increased by attaching tiny bumps or synapses of alumina, titanium dioxide and aluminum titanate on the surface of silicon nitride particles.

Benefits of technology

It significantly improves the wear resistance and pull resistance of the sheath material, extends the service life of the cable in harsh environments, and reduces safety hazards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119763912A_ABST
    Figure CN119763912A_ABST
Patent Text Reader

Abstract

The present application discloses a wear-resistant and tensile-resistant sheath material and cable. The sheath material comprises the following raw materials in parts by mass: 70-80 parts of EVA, 10-15 parts of PE, 24-31 parts of wear-resistant fillers, and 10-16 parts of glass fibers; 1.3-2.1 parts of silane coupling agent; the wear-resistant filler comprises silicon nitride particles and bonding enhancement attachments on the surface thereof, the bonding enhancement attachments are formed by mixing aluminum hydroxide and titanate and then sintering, the bonding enhancement attachments are tiny protrusions or synapses, which are dense, wear-resistant, and have strong bonding and adhesion with silicon nitride, thereby increasing the specific surface area of ​​the silicon nitride particles and the bonding and stabilizing anchor points with the organic phase, making the bonding of silicon nitride and the organic phase more closely connected, and the wear-resistant filler is not easy to peel off when the sheath material is worn, and acts as a better reinforcement anchor point when the sheath material is pulled, making the sheath material not easy to deform and break, so that the sheath material has better wear resistance and tensile resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to cable transmission, and in particular to a wear-resistant and tension-resistant sheath material and a cable. Background Art

[0002] As an important carrier for power transmission and information transfer, cables are widely used in various fields. However, in complex and changing use environments, the wear resistance and tensile resistance of cable sheaths often become key factors affecting their service life.

[0003] Although traditional cable sheath materials such as polyvinyl chloride (PVC) and polyethylene (PE) have certain wear resistance, they are still prone to wear and scratches after long-term use in harsh environments such as industrial automation, mining, and marine engineering, which can expose the internal lines of the cable and cause safety hazards. Therefore, it is particularly important to develop a cable sheath material with high wear resistance and tensile resistance. Summary of the invention

[0004] In order to extend the service life of the cable in a harsh environment, a wear-resistant and tensile-resistant sheath material and a cable are provided.

[0005] The above first invention objective of the present invention is achieved through the following technical solutions: A wear-resistant and tensile-resistant sheath material, comprising the following raw materials in parts by weight: EVA 70-80 parts, PE 10-15 parts, 24-31 parts of wear-resistant filler, 10-16 parts of glass fiber; 1.3-2.1 parts of silane coupling agent; The wear-resistant filler includes silicon nitride particles and bonding enhancement attachments attached to the surface of the silicon nitride particles. The bonding enhancement attachments are formed by mixing aluminum hydroxide and titanate and then sintering, and are convex points or synapses densely distributed on the surface of the silicon nitride particles.

[0006] By adopting the above technical scheme, liquid titanate can infiltrate aluminum hydroxide in the mixture and penetrate into aluminum hydroxide to form a covering material, and then the covering material is attached to the surface of silicon nitride and fired at 500-600°C. The aluminum hydroxide in the covering material is dehydrated and converted into aluminum oxide, and the titanate is decomposed to produce titanium dioxide. Since the aluminum hydroxide is infiltrated with titanate, the converted aluminum oxide is embedded with nano-titanium dioxide. The two are mixed evenly and tightly combined, and the aluminum oxide and titanium dioxide mixed together at high temperature partially react to form aluminum titanate, thereby further strengthening the aluminum oxide. The density of the combination with titanium dioxide and the tightness of the combination of aluminum oxide and titanium dioxide on the surface of silicon nitride are enhanced, so that the surface of silicon nitride is covered with a large number of tightly combined and wear-resistant tiny bumps or tiny synapses, which increase the specific surface area of ​​the silicon nitride particles and the firm anchor points of the combination with the organic phase, so that the silicon nitride and the organic phase are more tightly combined, and the wear-resistant filler is not easy to peel off when the sheath material is worn. When the sheath material is pulled, it serves as a better reinforcement anchor point to make the sheath material not easy to deform and break. Therefore, the sheath material of the present application has better wear resistance and tensile resistance.

[0007] Optional: The preparation method of the wear-resistant material is as follows: The silicon nitride particles and the coating diluted with ethanol are mixed evenly and then fired.

[0008] By adopting the above technical solution, ethanol in the covering material is used as a diluent to adjust the viscosity and volume of the covering material, so that the covering material can better cover the surface of the silicon nitride particles, and after the diluent evaporates, a point-distributed mixture of aluminum hydroxide and titanate is formed, which better forms tiny protrusions or synapses, and the resulting sheath material has better wear resistance and tensile resistance.

[0009] Optionally, the titanate is tetraisopropyl titanate.

[0010] By adopting the above technical solution, the viscosity of tetraisopropyl titanate and its wetting and penetration speed for aluminum hydroxide are more suitable. When mixed with aluminum hydroxide, the penetration and mixing effect of tetraisopropyl titanate is better, and the wear resistance and tensile resistance of the obtained sheath material are better.

[0011] Optionally, the aluminum hydroxide is a precipitate prepared by precipitating an aluminum salt under an alkaline environment.

[0012] By adopting the above technical solution, the density of aluminum hydroxide in the precipitate is lower, which makes it easier for titanate to penetrate, so that the mixing of aluminum oxide and titanium dioxide at the nano level is more homogeneous during high-temperature firing, and the resulting sheath material has better wear resistance and tensile resistance.

[0013] Optionally, the molar ratio of the aluminum hydroxide to the titanate is (2.1-2.5):1.

[0014] By adopting the above technical scheme, the proportion of alumina, titanium dioxide and aluminum titanate in the bonding reinforcement attachment is better under this ratio, and the hardness, wear resistance and bonding strength of the corresponding bonding reinforcement attachment to the silicon nitride surface are better, so that the wear resistance and tensile resistance of the obtained sheath material are better.

[0015] Optionally, the surface of the silicon nitride particles is hydrophilically modified by using carboxymethyl cellulose and polyvinyl pyrrolidone as dual modifiers.

[0016] By adopting the above technical solution, the surface of the silicon nitride particles is first modified to be hydrophilic, which is conducive to the adhesion of the coating material mixed with aluminum hydroxide and titanate to the surface of the silicon nitride, so that the tiny protrusions or tiny synapses are more evenly distributed on the surface of the silicon nitride and the bonding strength is higher, further improving the wear resistance and tensile resistance of the sheath material.

[0017] Optional: The modification method: Disperse polyvinyl pyrrolidone in water, then add silicon nitride and stir to mix thoroughly, then add carboxymethyl cellulose and stir on a heated stirring table at 60°C to completely dissolve the carboxymethyl cellulose; After ultrasonic treatment in a sonication bath for 20 min, the mixture was transferred to a ball mill for ball milling; The suspension is centrifuged to obtain a solid, which is washed with water, and the process is repeated several times to obtain carboxymethyl cellulose and polyvinyl pyrrolidone-modified silicon nitride particles.

[0018] By adopting the above technical solution, the ultrasonic treatment step is eliminated in the silicon nitride particle modification process, which is more suitable for the treatment of silicon nitride particles in batches of kilograms and improves the modification efficiency.

[0019] The above second invention objective of the present invention is achieved through the following technical solutions: A cable comprises a sheath layer, an insulating layer and a conductor, wherein the sheath layer is made of the above-mentioned sheath material.

[0020] By adopting the above technical solution, the outer sheath layer of the cable of the present application has excellent wear resistance and good tensile resistance, so that the service life of the cable in harsh environments is extended.

[0021] In summary, this application has at least the following beneficial effects: 1. A large number of tiny convex points or synapses formed by a uniform mixture of aluminum oxide, titanium dioxide, and aluminum titanate are attached to the surface of silicon nitride particles in the wear-resistant material. The tiny convex points or synapses are dense, wear-resistant, and have strong adhesion to silicon nitride, thereby increasing the specific surface area of ​​the silicon nitride particles and the solid anchor points for bonding with the organic phase, making the silicon nitride and the organic phase more tightly bonded. When the sheath material is worn, the wear-resistant filler is not easy to peel off. When the sheath material is pulled, it serves as a better reinforcement anchor point to make the sheath material less likely to deform and break. Therefore, the sheath material of the present application has better wear resistance and tensile resistance. 2. The surface of silicon nitride particles is first hydrophilically modified and then covered with a coating material mixed with aluminum hydroxide and titanate, so that tiny protrusions or tiny synapses are more evenly distributed on the surface of silicon nitride and have higher bonding strength, further improving the wear resistance and tensile resistance of the sheath material; 3. The outer sheath layer of the cable of the present application has excellent wear resistance and good tensile strength, which prolongs the life of the cable in harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the cross section of the cable.

[0023] Reference numerals 1. Conductor; 2. Insulation layer; 3. Filling rope; 4. Lining layer; 5. Armor layer; 6. Sheath layer. DETAILED DESCRIPTION

[0024] raw material EVA is Taiwan Plastics 7A60H product; PE is 5200B product of Yanshan Petrochemical; Silicon nitride, aluminum chloride, tetraethyl titanate, tetraisopropyl titanate, tetrabutyl titanate, and ethanol are all commercially available industrial-grade products.

[0025] Polyvinyl pyrrolidone is polyvinyl pyrrolidone K30, a product of Shandong Gushuo Biotechnology Co., Ltd.

[0026] Carboxymethyl cellulose is a commercially available product of Anhui Zhonghong Bioengineering Co., Ltd.

[0027] The glass fiber is alkali-free chopped glass fiber with a length of 4.5 mm and a diameter of 10 μm.

[0028] The silane coupling agent is dimethyldimethoxysilane, which is a commercially available industrial grade product.

[0029] Preparation Example 1 A wear-resistant filler, the specific preparation method of which is as follows: Add concentrated ammonia water to a 2.6 mol / L aluminum chloride solution to adjust the pH to 11.4, then filter to obtain a filtrate, wash the filtrate with water until the pH of the washing liquid is less than 7.1, and adjust the water content of the filtrate to 15 wt% by draining or adding water to obtain an aluminum hydroxide precipitate; Weigh 0.918 kg of aluminum hydroxide precipitate and 1.42 kg of tetraisopropyl titanate and mix them evenly to obtain a covering material; Take 10 kg of 8 μm silicon nitride, add 0.4 kg of covering material and 0.2 kg of ethanol, stir and mix evenly, then heat at 60°C for 2 hours, and remove the ethanol to obtain a mixture; The mixture was preheated at 80°C for 1 h, then heated to 540°C and heated under vacuum at 0.02 MPa for 7 h with stirring, and then cooled to obtain a wear-resistant filler.

[0030] Preparation Example 2 A wear-resistant filler is silicon nitride with a particle size of 8 μm.

[0031] Preparation Example 3 A wear-resistant filler, the specific preparation method of which is as follows: Add concentrated ammonia water to a 2.6 mol / L aluminum chloride solution to adjust the pH to 11.4, then filter to obtain a filtrate, wash the filtrate with water until the pH of the washing liquid is less than 7.1, and adjust the water content of the filtrate to 15 wt% by draining or adding water to obtain an aluminum hydroxide precipitate; Take 10 kg of 8 μm silicon nitride, add 0.4 kg of aluminum hydroxide precipitate and 0.2 kg of ethanol, stir and mix evenly, then heat at 60° C. for 2 h, and remove the ethanol to obtain a mixture; The mixture was preheated at 80°C for 1 h, then heated to 540°C and heated under vacuum at 0.02 MPa for 7 h with stirring, and then cooled to obtain a wear-resistant filler.

[0032] Preparation Example 4 A wear-resistant filler, the specific preparation method of which is as follows: Take 10 kg of 8 μm silicon nitride, add 0.4 kg of tetraisopropyl titanate and 0.2 kg of ethanol, stir and mix evenly, then heat at 60° C. for 2 h, and remove the ethanol to obtain a mixture; The mixture was preheated at 80°C for 1 h, then heated to 540°C and heated under vacuum at 0.02 MPa for 7 h with stirring, and then cooled to obtain a wear-resistant filler.

[0033] Preparation Example 5 A wear-resistant filler, the specific preparation method of which is as follows: 10 kg of polyvinyl pyrrolidone was added to 550 kg of water and mixed evenly to obtain a polyvinyl pyrrolidone dispersion. 10 kg of silicon nitride and 2.5 kg of carboxymethyl cellulose were added to the polyvinyl pyrrolidone dispersion and mixed evenly. The mixture was heated to 60° C. and stirred for 2 h until the carboxymethyl cellulose was completely dissolved. The mixture was heated to 72° C. and stirred for 2 h. The material was transferred to a ball mill and ball-milled at 460 rpm / min for 10 h to obtain a ball-milled material. The ball mill is centrifuged and then washed with clean water to separate the solid. The centrifugation and washing are repeated three times, and then dried and sieved. The solid with a particle size of 8 μm is selected to obtain modified silicon nitride. After multiple preparations, a sufficient amount is obtained and then mixed evenly for use; Add concentrated ammonia water to a 2.6 mol / L aluminum chloride solution to adjust the pH to 11.4, then filter to obtain a filtrate, wash the filtrate with water until the pH of the washing liquid is less than 7.1, and adjust the water content of the filtrate to 15 wt% by draining or adding water to obtain an aluminum hydroxide precipitate; Weigh 0.918 kg of aluminum hydroxide precipitate and 1.42 kg of tetraisopropyl titanate and mix them evenly to obtain a covering material; Take 10 kg of 8 μm modified silicon nitride, add 0.4 kg of covering material and 0.2 kg of ethanol, stir and mix evenly, then heat at 60° C. for 2 h, and remove ethanol to obtain a mixture; The mixture was preheated at 80°C for 1 h, then heated to 540°C and heated under vacuum at 0.02 MPa for 7 h with stirring, and then cooled to obtain a wear-resistant filler.

[0034] Preparation Example 6 A wear-resistant filler, the specific preparation method of which is as follows: 10 kg of polyvinyl pyrrolidone was added to 550 kg of water and mixed evenly to obtain a polyvinyl pyrrolidone dispersion. 10 kg of silicon nitride and 2.5 kg of carboxymethyl cellulose were added to the polyvinyl pyrrolidone dispersion and mixed evenly. The mixture was heated to 60° C. and stirred for 2 h until the carboxymethyl cellulose was completely dissolved. The mixture was heated to 72° C. and stirred for 2 h. The material was transferred to a ball mill and ball-milled at 460 rpm / min for 10 h to obtain a ball-milled material. After the ball mill is centrifuged, the solid is washed with clean water to separate. The centrifugation and washing are repeated three times, and then dried and sieved. Solids with a particle size of 8 μm are selected to obtain modified silicon nitride. After multiple preparations, a sufficient amount is obtained and then mixed evenly for use.

[0035] Preparation Example 7 A wear-resistant filler, the specific preparation method of which is as follows: 10 kg of polyvinyl pyrrolidone was added to 550 kg of water and mixed evenly to obtain a polyvinyl pyrrolidone dispersion. 10 kg of silicon nitride and 2.5 kg of carboxymethyl cellulose were added to the polyvinyl pyrrolidone dispersion and mixed evenly. The mixture was heated to 60° C. and stirred for 2 h until the carboxymethyl cellulose was completely dissolved. The mixture was heated to 72° C. and stirred for 2 h. The material was transferred to a ball mill and ball-milled at 460 rpm / min for 10 h to obtain a ball-milled material. After the ball mill is centrifuged, the solid is washed with clean water to separate. The centrifugation and washing are repeated three times, and then dried and sieved. Solids with a particle size of 8 μm are selected to obtain modified silicon nitride. After multiple preparations, a sufficient amount is obtained and then mixed evenly for use.

[0036] Add concentrated ammonia water to a 2.6 mol / L aluminum chloride solution to adjust the pH to 11.4, then filter to obtain a filtrate, wash the filtrate with water until the pH of the washing liquid is less than 7.1, and adjust the water content of the filtrate to 15 wt% by draining or adding water to obtain an aluminum hydroxide precipitate; Take 10 kg of 8 μm modified silicon nitride, add 0.4 kg of aluminum hydroxide precipitate and 0.2 kg of ethanol, stir and mix evenly, then heat at 60° C. for 2 h, and remove ethanol to obtain a mixture; The mixture was preheated at 80°C for 1 h, then heated to 540°C and heated under vacuum at 0.02 MPa for 7 h with stirring, and then cooled to obtain a wear-resistant filler.

[0037] Preparation Example 8 A wear-resistant filler, the specific preparation method of which is as follows: 10 kg of polyvinyl pyrrolidone was added to 550 kg of water and mixed evenly to obtain a polyvinyl pyrrolidone dispersion. 10 kg of silicon nitride and 2.5 kg of carboxymethyl cellulose were added to the polyvinyl pyrrolidone dispersion and mixed evenly. The mixture was heated to 60° C. and stirred for 2 h until the carboxymethyl cellulose was completely dissolved. The mixture was heated to 72° C. and stirred for 2 h. The material was transferred to a ball mill and ball-milled at 460 rpm / min for 10 h to obtain a ball-milled material. After the ball mill is centrifuged, the solid is washed with clean water to separate. The centrifugation and washing are repeated three times, and then dried and sieved. Solids with a particle size of 8 μm are selected to obtain modified silicon nitride. After multiple preparations, a sufficient amount is obtained and then mixed evenly for use.

[0038] Take 10 kg of 8 μm modified silicon nitride, add 0.4 kg of tetraisopropyl titanate and 0.2 kg of ethanol, stir and mix evenly, then heat at 60° C. for 2 h, and remove ethanol to obtain a mixture; The mixture was preheated at 80°C for 1 h, then heated to 540°C and heated under vacuum at 0.02 MPa for 7 h with stirring, and then cooled to obtain a wear-resistant filler.

[0039] Preparation Example 9 A wear-resistant filler, the specific preparation method of which is as follows: 10 kg of polyvinyl pyrrolidone was added to 550 kg of water and mixed evenly to obtain a polyvinyl pyrrolidone dispersion. 10 kg of silicon nitride and 2.5 kg of carboxymethyl cellulose were added to the polyvinyl pyrrolidone dispersion and mixed evenly. The mixture was heated to 60° C. and stirred for 2 h until the carboxymethyl cellulose was completely dissolved. The mixture was heated to 72° C. and stirred for 2 h. The material was transferred to a ball mill and ball-milled at 460 rpm / min for 10 h to obtain a ball-milled material. The ball mill is centrifuged and then washed with clean water to separate the solid. The centrifugation and washing are repeated three times, and then dried and sieved. The solid with a particle size of 8 μm is selected to obtain modified silicon nitride. After multiple preparations, a sufficient amount is obtained and then mixed evenly for use; Weigh 0.78 kg of commercially available 10 nm aluminum hydroxide powder, 0.138 kg of water, and 1.42 kg of tetraisopropyl titanate and mix them evenly to obtain a coating material; Take 10 kg of 8 μm modified silicon nitride, add 0.4 kg of covering material and 0.2 kg of ethanol, stir and mix evenly, then heat at 60° C. for 2 h, and remove ethanol to obtain a mixture; The mixture was preheated at 80°C for 1 h, then heated to 540°C and heated under vacuum at 0.02 MPa for 7 h with stirring, and then cooled to obtain a wear-resistant filler.

[0040] Preparation Example 10 A wear-resistant filler, which differs from Preparation Example 5 in that tetraethyl titanate and other substances are used to replace tetraisopropyl titanate, and the specific amount of tetraethyl titanate is 1.14 kg.

[0041] Preparation Example 11 A wear-resistant filler, which differs from Preparation Example 5 in that tetrabutyl titanate and other substances are used to replace tetraisopropyl titanate, and the specific amount of tetrabutyl titanate is 1.7 kg.

[0042] Preparation Example 12 A wear-resistant filler, which is different from Preparation Example 5 in that the covering material is obtained by mixing 0.918 kg of aluminum hydroxide precipitate and 1.893 kg of tetraisopropyl titanate.

[0043] Preparation Example 13 A wear-resistant filler, which is different from Preparation Example 5 in that the covering material is obtained by mixing 0.918 kg of aluminum hydroxide precipitate and 1.352 kg of tetraisopropyl titanate.

[0044] Preparation Example 14 A wear-resistant filler, which is different from Preparation Example 5 in that the covering material is obtained by mixing 0.918 kg of aluminum hydroxide precipitate and 1.136 kg of tetraisopropyl titanate.

[0045] Preparation Example 15 A wear-resistant filler, which is different from Preparation Example 5 in that the covering material is obtained by mixing 0.918 kg of aluminum hydroxide precipitate and 0.947 kg of tetraisopropyl titanate.

[0046] Preparation Example 16 A wear-resistant filler is different from Preparation Example 5 in that the mixed material preparation steps are as follows: 10 kg of 8 μm modified silicon nitride is added to 0.4 kg of covering material and stirred to mix evenly, and then the mixed material is heated at 60° C. for 2 hours.

[0047] Example 1 A wear-resistant and tensile-resistant sheath material, the raw materials of which are as follows: EVA 7.6kg, PE 1.4kg, Wear-resistant filler 2.8kg, Glass fiber 1.4kg, Silane coupling agent 0.18kg.

[0048] The wear-resistant filler is prepared in Preparation Example 1.

[0049] The preparation method of the wear-resistant and tensile-resistant sheath material is as follows: After the wear-resistant filler, glass fiber and silane coupling agent are uniformly mixed, they are evenly mixed with EVA and PE, and sent to a screw extruder for melt extrusion. The temperature of the melting zone is 135° C. to obtain a wear-resistant and tensile-resistant sheath material.

[0050] Embodiments 2 to 10 A wear-resistant and tensile-resistant sheath material, which differs from Example 1 in that the wear-resistant material used has a different source, as shown in Table 1.

[0051] Comparative Examples 1 to 6 A sheath material, which differs from Example 1 in that the wear-resistant material used is from a different source, as shown in Table 1.

[0052] Table 1. Sources of wear-resistant materials for Examples 1 to 10 and Comparative Examples 1 to 6 Source of wear-resistant materials Source of wear-resistant materials Example 1 Preparation Example 1 Example 3 Preparation Example 9 Comparative Example 1 Preparation Example 2 Example 4 Preparation Example 10 Comparative Example 2 Preparation Example 3 Example 5 Preparation Example 11 Comparative Example 3 Preparation Example 4 Example 6 Preparation Example 12 Example 2 Preparation Example 5 Example 7 Preparation Example 13 Comparative Example 4 Preparation Example 6 Example 8 Preparation Example 14 Comparative Example 5 Preparation Example 7 Example 9 Preparation Example 15 Comparative Example 6 Preparation Example 8 Example 10 Preparation Example 16 Embodiment 11 A wear-resistant and tensile-resistant sheath material, which differs from Example 2 in that the material dosage is as follows: EVA7kg, PE 1kg, wear-resistant filler 2.4kg, glass fiber 1kg, silane coupling agent 0.12kg.

[0053] Example 12 A wear-resistant and tensile-resistant sheath material, which differs from Example 2 in that the material dosage is as follows: EVA8kg, PE 1.5kg, wear-resistant filler 3.1kg, glass fiber 1.6kg, silane coupling agent 0.21kg.

[0054] The sheath materials of Examples 1 to 10 and Comparative Examples 1 to 6 were tested for wear resistance by relative volume abrasion according to GB / T 9867, and for tensile strength and tensile fracture rate according to GB / T1040 to evaluate tensile properties. The test results are shown in Table 2 below.

[0055] Table 2. Test results of Examples 1 to 10 and Comparative Examples 1 to 6 Combining Table 1 and Table 2, by comparing Example 1 with Comparative Examples 1 to 3, it can be seen that the relative volume wear of Example 1 is less than that of Comparative Examples 1 to 3, and the tensile strength and tensile fracture rate of Example 1 are greater than those of Comparative Examples 1 to 3. Therefore, the wear resistance and tensile strength of Example 1 are better than those of Comparative Examples 1 to 3.

[0056] The wear-resistant material of Example 1 is made of silicon nitride as a core and is coated with a bonding reinforcement attachment. The bonding reinforcement attachment is obtained by decomposing a covering material mixed with aluminum hydroxide and titanate at high temperature. When the covering materials are mixed, the liquid titanate infiltrates the aluminum hydroxide and penetrates into the aluminum hydroxide to form a covering material, which is then fired at 500-600°C. The aluminum hydroxide in the covering material is dehydrated and converted into aluminum oxide, and the titanate decomposes to produce titanium dioxide. Nano-titanium dioxide is embedded in the converted aluminum oxide, and the two are evenly mixed and tightly combined. The aluminum oxide and titanium dioxide parts mixed together at high temperature react to form aluminum titanate, thereby further strengthening the bonding density of aluminum oxide and titanium dioxide and enhancing the bonding tightness of the aluminum oxide and titanium dioxide mixture on the silicon nitride surface. As a result, the silicon nitride surface is covered with a large number of tightly combined and wear-resistant tiny bumps or tiny synapses, which increases the specific surface area of ​​the silicon nitride particles and the stable anchor point with the organic phase, so that the silicon nitride is more tightly combined with the organic phase, and the wear-resistant filler is not easy to peel off when the sheath material is worn. When the sheath material is pulled, it serves as a better reinforcing anchor point to make the sheath material not easy to deform and break, thereby making the sheath material have better wear resistance and tensile resistance.

[0057] Further comparison of comparative examples 1 to 3 shows that the relative volume wear of comparative example 1 is less than that of comparative examples 2 to 3, and the tensile strength and tensile fracture rate of comparative example 1 are greater than those of comparative examples 2 to 3, so the wear resistance and tensile strength of comparative example 1 are better than those of comparative examples 2 to 3.

[0058] The reason is that the covering materials in Comparative Examples 2 to 3 only decompose into aluminum oxide or titanium dioxide at high temperatures, lack the mutual filling of pores and increase in density between the two, lack the enhancement of the bonding strength of the decomposition products themselves and the bonding strength of the aluminum nitride surface by aluminum titanate, and the wear-resistant material preparation examples 3 to 4 used in Comparative Examples 2 to 3, after being combined with organic matter, the protrusions or synapses formed on the surface by a single aluminum oxide or a single titanium dioxide have low strength and poor adhesion, which in turn reduces the bonding between the silicon nitride particles and the organic phase. Therefore, the wear resistance and tensile resistance of the sheath materials in Comparative Examples 2 to 3 are not as good as those in Comparative Example 1 using silicon nitride without any modification.

[0059] It can be seen that the improvement in wear resistance and tensile strength achieved in Example 1 is obtained by sintering the covering material at high temperature to combine with the enhanced attachment, and the coexistence of aluminum hydroxide and titanate in the covering material and the sintering process are indispensable.

[0060] Combining Example 2 with Example 1, Example 2 has better wear resistance and tensile resistance than Example 1. For Example 2, the present application further improves on the basis of the wear-resistant material of Preparation Example 1, firstly improves the hydrophilicity of the surface of silicon nitride particles, and the coating material mixed with aluminum hydroxide and titanate is better attached to the surface of silicon nitride, so that the tiny protrusions or tiny synapses are more evenly distributed on the surface of silicon nitride and the bonding strength is higher. Therefore, Example 2 further improves the wear resistance and tensile resistance of the sheath material on the basis of Example 1.

[0061] Combined with Comparative Examples 1 to 6, it can be seen that: Comparative Example 4 uses hydrophilic modified silicon nitride particles on the basis of Comparative Example 1. The relative volume wear of Comparative Example 4 is greater than that of Comparative Example 1, and the tensile strength and tensile fracture rate of Comparative Example 4 are less than those of Comparative Examples 1 to 3. This is because without the high-temperature firing process and the reinforcement of the bonding reinforcement attachment, the hydrophilic modified silicon nitride particles have reduced compatibility with the organic phase, the wear-resistant material is easier to detach from the sheath material when it is worn, and the anchoring effect of the sheath material under tension is reduced; Comparative Examples 5 to 6 use hydrophilic modified silicon nitride particles as the substrate to attach a single aluminum oxide or a single silicon dioxide on the basis of Comparative Examples 2 to 3. The wear resistance and tensile resistance of Comparative Example 5 are not significantly improved compared with those of Comparative Example 2, and the wear resistance and tensile resistance of Comparative Example 6 are not significantly improved compared with those of Comparative Example 3. Therefore, when the silicon nitride particles are first hydrophilically improved, when the covering material is a single aluminum hydroxide or a single titanate, although its negative effects are avoided by high-temperature firing, it does not bring significant effective gains.

[0062] Therefore, for the present application, the effective gain of improving the hydrophilicity of silicon nitride particles can only be achieved on the basis of the combined enhanced attachment of aluminum hydroxide and titanate mixed firing.

[0063] Comparing Example 2 and Example 3, Example 3 uses commercially available aluminum hydroxide powder as the source of aluminum hydroxide in the covering material, while Example 2 uses newly converted aluminum hydroxide precipitate as the source of aluminum hydroxide in the covering material. The aluminum hydroxide in the precipitate has a lower density and is easier for titanate to penetrate, making the mixing of alumina and titanium dioxide at the nanometer level more homogeneous during high-temperature firing. The resulting sheath material has better wear resistance and tensile strength, which is reflected in the test results - the relative volume wear of Example 2 is less than that of Example 3, and the tensile strength and tensile fracture rate of Example 2 are greater than those of Example 3. Therefore, in the present application, the precipitate prepared by precipitating aluminum salt in an alkaline environment is better.

[0064] Comparing Example 2 with Examples 4 to 5, the difference between the three is that different titanates are used in the preparation of wear-resistant materials. In the test results, the relative volume wear of Example 2 is the smallest, and the tensile strength and tensile fracture rate of Example 2 are the largest. This is because tetraisopropyl titanate has a better viscosity and is more suitable for the infiltration and penetration speed of aluminum hydroxide, and has a better penetration and mixing effect when mixed with aluminum hydroxide. Therefore, tetraisopropyl titanate is preferably used as the titanate in this application.

[0065] Comparing Example 2 with Examples 6 to 9, it can be seen that the difference lies in the different molar ratios of aluminum hydroxide and titanate in the covering material. In the test results, the relative volume wear of Example 2 is the smallest, followed by Examples 8 and 9; the tensile strength and tensile fracture rate of Example 2 are the largest, followed by Examples 8 and 9. Therefore, when the molar ratio of aluminum hydroxide to titanate in the covering material in this application is (2.1 to 2.5): 1, the proportion of aluminum oxide, titanium dioxide, and aluminum titanate in the bonding enhancement attachment is better under this ratio, and the hardness, wear resistance, and bonding strength to the silicon nitride surface of the corresponding bonding enhancement attachment are better, so that the wear resistance and tensile resistance of the obtained sheath material are better.

[0066] By comparing Example 2 and Example 10, it can be seen that the covering material in Example 10 is not diluted with ethanol, but directly mixed with the modified silicon nitride particles. The covering material is unevenly distributed on the surface of the modified silicon nitride particles. After firing, there are fewer tiny protrusions and synapses, and more sheet-like covering film layers, with less increase in specific surface area. Therefore, the wear resistance and tensile resistance of the sheath material of Example 10 are not as good as those of Example 2. The relative volume wear of Example 10 is greater than that of Example 2, and the tensile strength and tensile fracture rate of Example 10 are less than those of Example 2.

[0067] In combination with Example 2 and Examples 11 to 12, Examples 11 to 12 have significantly lower relative volume wear, significantly greater tensile strength and tensile fracture rate than Comparative Examples 1 and 4. Therefore, the amount of raw materials used in the present application is controlled to be 70 to 80 parts by weight of EVA, 10 to 15 parts of PE, 24 to 31 parts of wear-resistant filler, and 10 to 16 parts of glass fiber; when the silane coupling agent is 1.3 to 2.1 parts, the sheath material of the present application has excellent wear resistance and tensile resistance.

[0068] Example 13 As attached Figure 1 As shown, a cable comprises a plurality of conductors 1. The conductors 1 are made of aluminum alloy or copper, and each conductor 1 is coated with an insulating layer 2.

[0069] Multiple conductors 1 are integrated into a cable bundle, and the gaps between the cable bundles are filled with filling ropes 3 to stabilize the positions between the conductors 1. In addition, the cable bundle is sequentially wrapped with an inner lining layer 4, an armor layer 5 and a sheath layer 6. The sheath layer 6 is obtained by plastic coating with one of the sheath materials in Examples 1 to 12.

[0070] The sheath layer 6 has excellent wear resistance and good tensile strength, which prolongs the service life of the cable in harsh environments.

[0071] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of protection required by the present invention, it will be protected by the patent law.

Claims

1. A wear-resistant and tensile-resistant sheath material, characterized in that: Including the following raw materials by mass: EVA 70~80 parts, PE 10~15 parts, Wear-resistant filler 24~31 parts, Glass fiber 10~16 parts; Silane coupling agent 1.3~2.1 parts; The wear-resistant filler includes silicon nitride particles and bonding enhancement attachments attached to the surface of the silicon nitride particles. The bonding enhancement attachments are formed by mixing aluminum hydroxide and titanate and then sintering, and are convex points or synapses densely distributed on the surface of the silicon nitride particles.

2. The wear-resistant and tensile-resistant sheath material according to claim 1, characterized in that: The preparation method of wear-resistant materials is as follows: The silicon nitride particles and the coating diluted with ethanol are mixed evenly and then fired.

3. The wear-resistant and tensile-resistant sheath material according to claim 1, characterized in that: The titanate is tetraisopropyl titanate.

4. The wear-resistant and tensile-resistant sheath material according to claim 1, characterized in that: The aluminum hydroxide is a precipitate prepared by precipitation of aluminum salt under alkaline environment.

5. The wear-resistant and tensile-resistant sheath material according to claim 1, characterized in that: The molar ratio of the aluminum hydroxide to the titanate is (2.1-2.5):

1.

6. The wear-resistant and tensile-resistant sheath material according to claim 1, characterized in that: The surfaces of the silicon nitride particles are hydrophilically modified by using carboxymethyl cellulose and polyvinyl pyrrolidone as double modifiers.

7. The wear-resistant and tensile-resistant sheath material according to claim 6, characterized in that: The modification method: Disperse polyvinyl pyrrolidone in water, then add silicon nitride and stir to mix thoroughly, then add carboxymethyl cellulose and stir on a heated stirring table at 60°C to completely dissolve the carboxymethyl cellulose; After ultrasonic treatment in a sonication bath for 20 min, the mixture was transferred to a ball mill for ball milling; The suspension is centrifuged to obtain a solid, which is washed with water, and the process is repeated several times to obtain carboxymethyl cellulose and polyvinyl pyrrolidone-modified silicon nitride particles.

8. A cable, comprising a sheath layer (6), an insulating layer (2) and a conductor (1), characterized in that: The sheath layer (6) is made of the sheath material described in any one of claims 1 to 7.

Citation Information

Cited By

  • Corrosion-resistant electric wire and cable for deep sea and preparation method and application of corrosion-resistant electric wire and cable

    CN120590703A

  • Steel wire reinforced core overhead insulated cable

    CN120727355A